ANALISIS EFISIENSI BENTUK LEMAH DALAM PASAR MODAL DEVELOPED, EMERGING, DAN FRONTIER ANALYSIS OF WEAK EFFICIENCY IN DEVELOPED, EMERGING AND FRONTIER CAPITAL MARKETS - Sihombing, Elisabeth; Sukmadilaga, Citra (Jurnal Ekonomi dan Bisnis, 2018)
The Weak Efficient Market shows that the prices of securities fully reflect past information. The purpose of this research to analyze the efficiency of the weak form related to the random walk theory in three capital market classifications, namely developed, emerging, and frontier. This study uses a daily closing stock price index from the capital market index of each market classification. The research period began from January 1, 2002 to March 31, 2016 and was divided into three periods; before, during and after the global financial crisis. The Tests conducted in this research include the Kolmogorov-Smirnov test, the run test, the autocorrelation test, and the variance ratio test. The results of this research indicate the efficiency of weak forms in developed and emerging markets in different periods, while the frontier markets show inefficiencies